A tryptophan metabolite of the skin microbiota attenuates inflammation in patients with atopic dermatitis through the aryl hydrocarbon receptor - Yu, Jinlei; Luo, Yang; Zhu, Zhenlai; Zhou, Yufeng; Sun, Licheng; Gao, Jixin; Sun, Jinlv; Wang, Gang; Yao, Xu; Li, Wei (Journal of allergy and clinical immunology, 2019)
Previous studies have revealed significant alterations in the skin microbiota of patients with atopic dermatitis (AD) not only in diversity and composition but also in function, and the tryptophan (Trp) metabolic pathway is attenuated in the skin microbiota of patients with AD. We sought to assess Trp metabolites on the skin surfaces of patients with AD and to explore the function of the microbial Trp metabolites in skin inflammation in patients with AD. A gel-patch method was developed to collect metabolites on the skin surface, which were then assessed by using liquid chromatography–tandem mass spectrometry. A mouse model of calcipotriol (MC903)–induced AD-like dermatitis was used to evaluate the effects of microbial metabolites on AD, and aryl hydrocarbon receptor (AhR)–null mice and keratinocyte cultures were used to investigate the mechanism. Major microbial metabolites of Trp were detected on the skin surfaces of healthy subjects, and the level of indole-3-aldehyde (IAId), an indole derivative of Trp catabolism, was significantly lower in lesional and nonlesional skin of patients with AD than that of healthy subjects. IAId significantly attenuated skin inflammation in mice with MC903-induced AD-like dermatitis, and this effect was blocked by an AhR antagonist and abolished in AhR-null mice. Furthermore, IAId was found to inhibit the MC903-induced expression of thymic stromal lymphopoietin in keratinocytes in vivo and in vitro, which was mediated by binding of AhR to the thymic stromal lymphopoietin promoter. IAId, a skin microbiota–derived Trp metabolite, negatively regulated skin inflammation in patients with AD, revealing that skin microbiota play a significant functional role in the pathogenesis of AD. [Display omitted]